2000
DOI: 10.1038/sj.leu.2401755
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic trioxide (As2O3) gradually downregulates tissue factor expression without affecting thrombomodulin expression in acute promyelocytic leukemia cells

Abstract: Arsenic trioxide (As 2 O 3 ) was shown to induce complete remission in a high proportion of patients with relapsed and all-trans retinoic acid (ATRA)-resistant acute promyelocytic leukemia (APL). 1 The clinical response to As 2 O 3 is associated with the induction of nonterminal cytodifferentiation and the activation of cysteine proteases (caspases) that are characteristic of apoptosis. We have recently found that vitamin A derivatives, retinoids such as ATRA, exert anticoagulant effects by upregulating thromb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…In APL patients receiving As 2 O 3 treatment, the improvement of disseminated intravascular coagulation (DIC) or hyper®brinolysis paralleled the amelioration of bleeding symptoms, the correction of plasma ®brinogen level, and the decrease in membrane procoagulant activity (PCA) as well as TF contents of APL blasts Agis et al, 1999). Consistent with the in vivo ®ndings, the membrane PCA and TF at both protein and mRNA levels in APL cell line NB4 were rapidly down-regulated by 1 mM As 2 O 3 Ohsawa et al, 2000).…”
Section: Improvement Of Bleeding Diathesis With As 2 O 3 Treatmentsupporting
confidence: 61%
“…In APL patients receiving As 2 O 3 treatment, the improvement of disseminated intravascular coagulation (DIC) or hyper®brinolysis paralleled the amelioration of bleeding symptoms, the correction of plasma ®brinogen level, and the decrease in membrane procoagulant activity (PCA) as well as TF contents of APL blasts Agis et al, 1999). Consistent with the in vivo ®ndings, the membrane PCA and TF at both protein and mRNA levels in APL cell line NB4 were rapidly down-regulated by 1 mM As 2 O 3 Ohsawa et al, 2000).…”
Section: Improvement Of Bleeding Diathesis With As 2 O 3 Treatmentsupporting
confidence: 61%
“…As a differentiation therapy, ATO induces APL cell differentiation by degrading the PML-RARα fusion protein. Studies have shown that TF and procoagulant activity were significantly decreased in ATO-treated APL cells [15,16]. There are also reports that observed a significant reduction in Pn generation on ATO-treated APL cells [12].…”
Section: Introductionmentioning
confidence: 94%
“…Since arsenic trioxide was shown to induce maturation of ATRA-resistant APL cells (Chen et al, 1996) and was eectively used to treat ATRA-resistant APL relapses Shen et al, 1997;Bergstrom et al, 1998), numerous investigations have been designed to determine its mechanisms of action (MuÈ ller et al, 1998;Shao et al, 1998;Dai et al, 1999;Koken et al, 1999;Sternsdorf et al, 1999;Ohsawa et al, 2000;Kitamura et al, 2000a). This aspect is exhaustively reviewed by others in this issue.…”
Section: Synergistic Responses To Arsenic-atramentioning
confidence: 99%